Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan - Astiandini Hidayatullah; Sri Surjani Tjahjawati (Jurnal Riset Bisnis dan Investasi, 2017)
This research was conducted to find out how the process of implementation of safety and health program in the production director detail part manufacturing division PT Dirgantara Indonesia, this research also can be known about work productivity at PT Dirgantara Indonesia. This research was conducted on 117 respondents who are employees of the production director detail part manufacturing division PT Dirgantara Indonesia. This study used primary data by using questionnaires and interviews also using secondary data obtained from books and journals. The classical principle test used for this research is normality test, heteroscedasticity test, and linearity test. The result is employee productivity in productivity direktorat production detail part manufacturing division PT Dirgantara Indonesia of 27.1% made by the implementation of health and safety programs as much as 72.9%. The result of hypothesis test shows that there is significant influence between the implementation of work safety program to the work productivity of the employees of the production directorate part manufacturing PT Dirgantara Indonesia.